ANALISIS PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN DAN KARAKTERISTIK ORGANISASI TERHADAP KINERJA KARYAWAN PT. TRANS NUSANTARA BORNEO - Dayat Ikhsan Hajati (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2018)
The aims of this research were 1) to analyze the significant effect of individual characteristics on employees’ performance partially, 2) to analyze the significant effect of job characteristics on employees’ performance partially, 3) to analyze the significant effect of organizational characteristics on employees’ performance partially, 4) to analyze the significant effect of individual characteristics, job characteristics and organizational characteristics on employees’ performance simultaneously. The types of research was causal research. The populations were employees at PT. Trans Nusantara Borneo (TNB), with 30 peoples as samples in this research and sampling technique uses saturated sampling technique. The method of data analysis used multiple regression analysis. The results of research showed that individual characteristics have insignificant effect on employees’ performance partially. Job characteristics and organizational characteristics have significant effect on employees’ performance partially. Individual characteristics, job characteristics and organizational characteristics have significant effect on employees’ performance simultaneously.                                                            Keywords: Individual Characteristics, Job Characteristics, Organizational Characteristics, Employees’ Performance.